2021
DOI: 10.3390/molecules26113421
|View full text |Cite
|
Sign up to set email alerts
|

Review on Bee Products as Potential Protective and Therapeutic Agents in Male Reproductive Impairment

Abstract: Bee products are sources of functional food that have been used in complementary medicine to treat a variety of acute and chronic illnesses in many parts of the world. The products vary from location to location as well as country to country. Therefore, the aim of this review was to identify various bee products with potential preventive and therapeutic values used in the treatment of male reproductive impairment. We undertook a vigorous search for bee products with preventive and therapeutic values for the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 98 publications
(103 reference statements)
0
11
0
1
Order By: Relevance
“…Accordingly, numerous natural products, including bee products, have established a presence on market shelves and have begun to garner consumer interest. The bee products include honey, bee pollen, bee bread, royal jelly, beeswax, bee venom, apilarnil and beeswax [ 3 ]. One of these products, bee pollen, is collected from plant flowers by the honey bee.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, numerous natural products, including bee products, have established a presence on market shelves and have begun to garner consumer interest. The bee products include honey, bee pollen, bee bread, royal jelly, beeswax, bee venom, apilarnil and beeswax [ 3 ]. One of these products, bee pollen, is collected from plant flowers by the honey bee.…”
Section: Introductionmentioning
confidence: 99%
“…RJ, a viscous secretion of A. mellifera worker bees, is considered an important functional natural product with a wide range of commercial, cosmetic and medical applications [ 10 ]. Moreover, in modern medicine, RJ has been demonstrated various pharmacological properties such as antioxidant, anti-inflammatory, immunomodulatory, nephroprotective, wound-healing, and antimicrobial effects [ 11 – 14 ]. The present study was aimed at evaluating the antitumor effects of royal jelly obtained from A. mellifera compared with cyclophosphamide (CP), as an alkylating agent which is widely used for the treatment of neoplastic cancers, against the Ehrlich solid tumors (EST) in mice.…”
Section: Resultsmentioning
confidence: 99%
“…RJ samples were dissolved with normal saline and filtered under a vacuum by means of filter paper (Whatman membrane, England) to reach the doses of 200 and 400 mg/kg. The selection of these concentrations was based on the previous study that showed promising biological effects with minimum toxicity [ 14 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The type of plants used by the bees and the season had a strong effect on the chemical composition of propolis [98,[111][112][113]. Therefore, [114] reported that the propolis in temperate zones differs in its chemical composition.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%